Gastro-Esophageal Reflux Disease and Paroxysmal Atrial Fibrillation Ablation - Mariana Floria; Diana-Elena Iov; Daniela Maria Tanase; Oana Bogdana Barboi; Genoveva Livia Baroi; Alexandru Burlacu; Mihaela Grecu; Radu Andy Sascau; Cristian Statescu; Catalina Mihai; Vasile Liviu Drug (Life, 2023)
Patients undergoing ablation for atrial fibrillation may be at increased risk of developing gastroesophageal reflux disease. We prospectively studied the presence of symptomatic gastroesophageal reflux disease in naïve patients who underwent atrial fibrillation ablation. Methods: The presence of typical symptoms suggestive of gastroesophageal reflux disease was clinically assessed by the gastroenterologist at baseline and at 3 months after ablation. In addition to that, all patients underwent upper gastrointestinal endoscopy. Results: Seventy-five patients were included in two groups: 46 patients who underwent atrial fibrillation ablation (study group) and 29 patients without ablation (control group). Patients with atrial fibrillation ablation were younger (57.76 ± 7.66 years versus 67.81 ± 8.52 years; p = 0.001), predominantly male (62.2% versus 33.3%; p = 0.030) and with higher body mass index (28.96 ± 3.12 kg/m2 versus 26.81 ± 5.19 kg/m2; p = 0.046). At three months after the ablation, in the study and control groups, there were 88.9% and 57.1% patients in sinus rhythm, respectively, (p = 0.009). Symptomatic gastroesophageal reflux disease was not more frequent in the study group (42.2% versus 61.9%; p = 0.220). There was no difference in terms of sinus rhythm prevalence in patients with versus without symptomatic gastroesophageal reflux disease (89.5% versus 88.5%; p = 0.709). Conclusion: In this small prospective study, typical symptoms suggestive of gastroesophageal reflux disease were not more frequent three months following atrial fibrillation ablation.